A new species of Barbatula from the Russian Altai (Teleostei: Nemacheilidae) - Prokofiev, Artem M. (Zootaxa, 2015)
Barbatula restricta, new species, is described from the Saldan-Kol Lake in the upper Ob River drainage in the Altai Mountains. It is distinguished from all other species of Barbatula in Asia by its body depth increasing continuously between the nape and the dorsal-fin origin and a combination of characters: nares widely spaced, upper lip with a short medial incision, lower lip without lateral expansions, mental lobes of lower lip without conical protrusions, tips of paired fins formed by 1st and 2nd branched rays, 42–45 (mean 44) vertebrae, color pattern consisting of small irregular mottles without saddles on back. An overview of the status of all nominal Asiatic Barbatula species described is given.